ANALISIS KUALITAS BUAH JAMBU KRISTAL (PSIDIUM GUAJAVA L) DI LEUKOPO IPB, BOGOR) - Kristina Irnasari Naikofi (CV. Multi Kreasi Media, 2023)
Crystal guava ripening is one of the most important processes in the fruit, which involves changes in color, taste and texture that make the fruit acceptable for consumption. Several physiological, biochemical and structural changes occur during fruit ripening, including breakdown of starch or other polysaccharides, production of sugars, synthesis of pigments and aromatic compounds, and partial softening of the cell wall. In climacteric fruits, these changes occur within a short time, and crystal guava, which is a climacteric fruit, shows increased respiration and ethylene production during ripening. Crystal guava also contains carotenoids and polyphenols which are the main antioxidant pigments in plants because they have medicinal effects. Crystal guava fruit, leaves, roots and bark are used in traditional medicine to cure gastroenteritis, asthma, high blood pressure, obesity and diarrhea. Observation of crystal guava fruit was carried out at the IPB Leuwikopo experimental garden from September to mid-December 2019. The purpose of this study was to determine the quality analysis of crystal guava fruit. In conclusion, the levels of chlorophyll a, chlorophyll b, and carotenoids were higher in old leaves compared to young leaves, while the anthocyanin levels in young leaves were higher than old leaves.